Early communicative gestures and play as predictors of language development in children born with and without family risk for dyslexia. Issue 4 (29th April 2014) - Unhjem, Astrid; Eklund, Kenneth; Nergård‐Nilssen, Trude
<x xml:space="preserve">Abstract</x> The present study investigated early communicative gestures, play, and language skills in children born with family risk for dyslexia (FR) and a control group of children without this inheritable risk at ages 12, 15, 18, and 24 months. Participants were drawn from the Tromsø Longitudinal study of Dyslexia (TLD) which follows children's cognitive and language development from age 12 months through Grade 2 in order to identify early markers of developmental dyslexia. Results showed that symbolic play and parent reported play at age 12 months and communicative gestures at age 15 months explained 61% of the variance in productive language at 24 months in the FR group. These early nonlinguistic measures seem to be potentially interesting markers of later language development in children born at risk for dyslexia.